Human Peripheral Blood Mononuclear Cells Proliferation and Secretion of Type I Interferon after Treatment with Polyherbal Formulations Fractions - Abubakar-Babangida Usman; Kabir-Magaji Hamid; Muawiya Abubakar; Ronaldson-Arinze Achigbo; Hauwa-Mummy Abdulrahman; Mohammed-Haruna Yeldu; Umar Zulkfilu; Mustapha-Umar Imam; Mansur Aliyu; Nura-Kaoje Abubakar (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Human immunodeficiency virus (HIV) infections are becoming resistant to therapy, despite extensive discoveries. The use of natural remedies for HIV treatment is becoming global. This study evaluates the in-vitro effect of aqueous extract of polyherbal formulation (PHF) fractions on peripheral blood mononuclear cells (PBMCs) proliferation and secretion level of type 1 interferons. Methods. Column chromatography of the PHF yielded four fractions (A, B, C, and D). Different concentrations (25 µg/ml, 50 µg/ml, 100 µg/ml, and 200 µg/ml) of each fraction were prepared. A blood sample from a newly diagnosed HIV-positive volunteer was used. The percentage viability, cytotoxicity, and proliferation of the PBMCs were determined using the trypan blue dye exclusion method and WST-8 assay respectively. Results. The viability of the PBMC significantly decreased with increasing concentrations of each PHF fraction (P=0.0001). While fraction D exhibits the highest percentage of cytotoxicity, 16.17% at 200 g/ml, fraction C exhibits the lowest percentage of cytotoxicity at 25 g/ml concentration and upregulate interferons expression (IFN-α, IFN-β). Fractions A, B, and C induces significant PBMC proliferation (P 0.0001). Conclusion. The fractions have proliferative potential and enhance interferon production. In-depth PHF fractions and structural studies of the bioactive compounds are recommended.